Shifting Among The Noble Teenagers of Mambalan Village Gunung Sari - Abdussamad, Zainudin Abdussamad; Machmoed, Hamzah A.; Pammu, Abidin; Sahib, Harlina (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This study aims to reveal the phenomenon of language shift among the noble teenagers of mambalan Village. Research has been carried out with the noble teenagers as the participants of this research. To improve understanding of the complexity of this research, this research used descriptive qualitative method by using some tools in collecting the data such as, questionnaires, interview, data recording, note taking and observation. After obtaining the data, the data analyzed by Gathering and understanding data transcription carefully, coding the data transcription word per word and displaying the words into the relevant conversation. The study found that there is language shift occurred among the noble teenagers of mambalan village. The finding is strengthened by vocabularies and sentences which shifted from high Sasak language to low Sasak language.